2018
DOI: 10.1002/stem.2931
|View full text |Cite
|
Sign up to set email alerts
|

Step-Wise Chondrogenesis of Human Induced Pluripotent Stem Cells and Purification Via a Reporter Allele Generated by CRISPR-Cas9 Genome Editing

Abstract: The differentiation of human induced pluripotent stem cells (hiPSCs) to prescribed cell fates enables the engineering of patient-specific tissue types, such as hyaline cartilage, for applications in regenerative medicine, disease modeling, and drug screening. In many cases, however, these differentiation approaches are poorly controlled and generate heterogeneous cell populations. Here we demonstrate cartilaginous matrix production in three unique hiPSC lines using a robust and reproducible differentiation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
105
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 83 publications
(112 citation statements)
references
References 65 publications
(73 reference statements)
7
105
0
Order By: Relevance
“…The results of scRNA-seq of sorted cells revealed that cells positive for PDGFRb, CD146, and CD166 exhibited enhanced cell homogeneity with decreased neurogenic subpopulations. These findings support the hypothesis that sorting of hiPSC-derived chondroprogenitor cells using surface markers can be used to purify progenitor cells with enhanced chondrogenic potential, without the need for genetic modification to improve hiPSC chondrogenesis (Adkar et al, 2018;Diekman et al, 2012).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The results of scRNA-seq of sorted cells revealed that cells positive for PDGFRb, CD146, and CD166 exhibited enhanced cell homogeneity with decreased neurogenic subpopulations. These findings support the hypothesis that sorting of hiPSC-derived chondroprogenitor cells using surface markers can be used to purify progenitor cells with enhanced chondrogenic potential, without the need for genetic modification to improve hiPSC chondrogenesis (Adkar et al, 2018;Diekman et al, 2012).…”
Section: Discussionsupporting
confidence: 80%
“…We previously reported that chondroprogenitor cells at the end of mesodermal lineage differentiation had high expression of CD146 and CD166 (Adkar et al, 2018). In the present study, we observed that these markers were also highly co-expressed with COL2A1.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…With the advent of a multitude of new methods for cellular engineering, we propose that a new generation of stem cell therapies will emerge that can provide functional tissue replacements as well as exogenous or even self‐regulating capabilities for biologic drug delivery. In addition to such therapeutic applications of stem cells in vivo, genome edited stem cells may also allow for the development of in vitro models of disease or reporter systems for stem cell purification or for investigating the consequences of causative or associate genetic elements such as coding/noncoding single nucleotide polymorphisms, variable number tandem repeats, and so forth identified through genome‐wide association studies …”
Section: Discussionmentioning
confidence: 99%